P093: Sound check: quality in point of care ultrasound in rural and regional Saskatchewan through participatory action research. (15th May 2017) - Moshynskyy, A.I.; Kapusta, M.; McGonigle, R.; Miller, L.; O'Brien, J.M.; Thoma, B.; Vertue, P.; Olszynski, P.
Abstract : Introduction: In the rural setting, Point-of-Care Ultrasound (POCUS) can dramatically impact rural acute care. In Saskatchewan, many rural clinicians have undertaken POCUS training, but widespread integration into rural emergency care remains elusive. We aimed to explore of the obstacles limiting adoption and their possible solutions to inform the development of a robust and innovative rural POCUS program in Saskatchewan.Methods: We conducted a mixed methods Participatory Action Research (PAR) study using surveys and focus groups. Our rural co-investigators identified 4 key realms relating to rural POCUS use: equipment, access to training, quality assurance (QA), and research. These guided the design of an online survey sent out to rural clinicians throughout Saskatchewan. Results of the survey informed the development of three approaches (centralized, hub-and-spoke, and decentralized) to training, QA, and research which were discussed at focus group sessions held at Saskatchewan's Emergency Medicine Annual Conference (Regina, SK. 2016). The focus groups were facilitated by the study investigators. Responses were analyzed using a simple thematic analysis to identify relevant themes and subthemes.Results: 34 rural clinicians responded to the online survey. There was general agreement that POCUS is valuable in rural acute care, training is difficult to access and should be standardized, and that QA and research are desired but impractical in the current environment. 11 rural clinicians attended the focus groups. Analysis of focus groups yielded seven distinct themes/needs: infrastructure needs, peer networks, common standards, both local and regional training opportunities, academic support, access to resources, and culture change. Seventeen sub-themes were identified and noted as having either a positive or negative and direct or indirect effect on the above themes. Broadly speaking, participants supported a distributed "spoke-hub" model where training, research and QA occurs within distributed, regional hubs with support from academic sites.Conclusion: The adoption of POCUS for emergency care in rural Saskatchewan faces significant opportunities and obstacles. There is interest on the part of rural clinicians to overcome these challenges to improve patient care.